Bridge of Tomorrow, New York World's Fair 1939 (Grinnell Litho Co.)
Connecting the Administration Building with the main exhibit area of the Fair, the "Bridge of Tomorrow" creates a new architectural design by utilizing the smooth curves and flowing lines of nautical construction.